Identification and characterization of the powdery mildew resistance in a spelt accession Lsy-93 - Nina Sun; Jiatong Li; Jiansheng Lu; Ningning Yu; Hongxing Xu; Qingpeng Sun; Tangyu Yuan; Jiadong Zhang; Linzhi Li; Huanchun Zhang; Yuli Jin; Pengtao Ma (BMC Plant Biology)
Abstract Background Powdery mildew, a widespread fungal disease caused by Blumeria graminis f. sp. tritici (Bgt), seriously threatens the yield and quality of wheat. The most effective and sustainable approach to control this disease is utilizing resistance genes and unraveling their underlying molecular mechanisms. Spelt (Triticum aestivum ssp. Spelta, 2n = 6x = 42, AABBDD), an ancient hexaploid wheat subspecies, has emerged as a valuable genetic resource for enhancing powdery mildew resistance in modern wheat breeding programs. Results Spelt accession lsy-93 demonstrated resistance against powdery mildew at the whole-growth stage. Genetic analysis revealed that the seedling resistance is conferred by a single dominant gene, tentatively designated as PmLsy-93. Bulked segregant RNA sequencing (BSR-seq) and molecular markers positioned PmLsy-93 within a 1.5 cM (genetic) and 10.34 Mb (physical) interval on chromosome 2BL. Six genes were directly associated with disease resistance in this interval and hence were considered as the candidate genes for PmLsy-93. Furthermore, a total of 3,140 differentially expressed genes (DEGs) were identified between the two bulks, with 2,214 down-regulated and 916 up-regulated ones relative to the susceptible bulk. The integration of gene ontology and kyoto encyclopedia of genes and genomes pathway analysis underscores the multifaceted roles of these DEGs in plant defense, stress response, and metabolic regulation. Then, expression pattern of six genes, encoding disease resistance protein, serine threonine-protein kinase, or protein kinase domain, were profiled with Bgt invasion, and analyzed their potential roles in immune pathway. Three closely linked or co-segregated markers were confirmed to be available for marker-assisted selection of PmLsy-93 in breeding programs. Conclusions This study successfully pinpointed critical genetic loci and candidate genes associated with powdery mildew resistance in the spelt wheat accession Lsy-93. The results provide valuable insights into plant-pathogen defense mechanisms and lay an foundation for subsequent molecular breeding efforts to enhance crop disease resistance.